(untitled) (Communications in Computational Physics, 2020)
Flux coordinates and field-line coordinates are ubiquitous in magnetically confined plasma research. Most of these coordinates are essentially non-orthogonal curvilinear coordinates, in which the differential operators are rather complicated. This article reports an automatic tool, OpGen, for generating a finite difference coefficient matrix for field solvers by using a computer symbolic computation system. This tool is suitable for, but is not limited to, code development for toroidally confined plasmas.